Agriculture and Climate Change Policy Brief: Main Issues for the UNFCCC and Beyond - Meridian Institute; Lee, D. (Meridian Institute, 2011)
This summary is a condensed version of the June 2011 Agriculture and Climate Change: A Scoping Report developed by a team of expert authors, in consultation with UN Framework Convention on Climate Change (UNFCCC) negotiators and other key stakeholders, and facilitated by Meridian Institute. The aim of that report was to provide independent, objective analysis on many complex issues related to agriculture and climate change. This summary provides key points for policymakers, focusing on the unique aspects of agriculture when considered in the context of climate change. It recommends actions that can be taken when considering agriculture s multiple objectives, from providing adequate food for growing populations to protecting the environment, and ensuring resilience to future climatic change. Finally, it briefly describes needs related to finance, technology, and capacity building; options for measuring mitigation and adaptation activities; and trade dimensions.